Performance enhancement of an out-of-plane electret-based vibrational energy harvester with dual charged plates - Tao, Kai (2018)
This paper presents a novel out-of-plane electret-based vibrational power generator (EVPG) that has both negative and positive charged electret plates integrated into a single seismic mass system. Compared with the conventional single-charged two-plate configuration, the proposed device not only exhibits an enhanced output voltage magnitude but also has a wide operational bandwidth due to spring softening nonlinearity according to the experimental analysis. With the acceleration changes from 0.1g to 0.5g, the operating 3-dB bandwidth can be increased 2.6 times from 2.5 Hz to 6.5 Hz, which indicates higher energy conversion efficiency than a linear energy harvester in the practical scenario of broadband random vibrations.